Neuroimaging of Voice Hearing in Non-Psychotic Individuals: A Mini Review - Diederen, Kelly M.; Van Lutterveld, Remko; Sommer, Iris (Frontiers in Human Neuroscience, 2012)
Auditory verbal hallucinations (AVH) or ‘voices’ are a characteristic symptom of schizophrenia, but can also be observed in healthy individuals in the general population. As these non-psychotic individuals experience AVH in the absence of other psychiatric symptoms and medication-use they provide an excellent model to study AVH in isolation. Indeed a number of studies used this approach and investigated brain structure and function in non-psychotic individuals with AVH. These studies showed that aberrant connectivity of language production and perception areas is particularly associated with AVH. This is in concordance with investigations that observed prominent activation of these language areas during the state of AVH. Effortful attention decreased cerebral dominance for language and dopamine dysfunction on the other hand, are presumably not specifically related to AVH.